Implementasi Pendekatan Saintifik Kurikulum 2013 pada Pembelajaran IPA di SD/MI Kelas IV - Suparlan Suparlan (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2017)
Elementary school (SD) Of Muhammadiyah Demangan Yogyakarta is featured SD. It is seen from the miraculous achievements of students both at provincial and national levels, adequate infrastructure, a spirit of community to send their children in elementary school. Accordingly, of course, can not be separated from the role of teachers as educators and counselors to provide services in the classroom and outside the classroom. Muhammadiyah elementary schools including one school are designated by the ministry of religion (MORA) to implement the curriculum by 2013. Therefore it is necessary to do research on the implementation of the scientific approach in science (IPA) learning curriculum in 2013. Type of research is qualitative lookups. As for the subject of this research is that teachers and students in the fourth grade (IV) of Muhammadiyah elementary school Demengan Yogyakarta. data collection by interview, documentation and observation. the process of data analysis, namely: examining the data, data reduction, and data presentation. he results of this research : (1) teachers in SD Muhammadiyah alreadyunderstand and know the theory of scientific approach, steps in learning. As for the understanding of the scientific approach according to the fourth grade (IV) of Muhammadiyah elementary school teachers, Mr Kastowo